Systematic Literature Review: Intervention for Behaviour Problems of Young Children with Autistic Spectrum Disorder (ASD) - Dede Supriyanto (The Center for Disability Studies and Services Brawijaya University, 2020)
This paper presents a review of research on intervention of behaviour problem in young children with Autistic Spectrum Disorder (ASD) between 2002 and 2019. 15 literatures include in this review based on inclusion and exclusion criteria that involves 490 participants. The analysis is categorized into Three Theme: 1) the behaviour problem that exist most in young children with ASD, 2) The intervention overview, and 3) the intervention outcome. The analysis results a recommendation that various approach and method in this review is effective to reduce behaviour problem as well as improve appropriate behaviour.